Is chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) in children the same condition as in adults?. (26th August 2018) - Sa, Mario; Green, Lydia; Abdel‐Mannan, Omar; Chong, W K Kling; Jacques, Thomas; Clarke, Antonia; Childs, Anne‐Marie; Lim, Ming; Hemingway, Cheryl; Hacohen, Yael
Abstract : This case series describes three children with chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS), an inflammatory condition characterized by a relapsing–remitting disease course responsive to steroids. The patients (two males, age 3y and 13y; one female, age 14y) presented with ataxia, dysarthria, and multiple cranial neuropathies. All patients demonstrated bilateral nodular lesions with contrast enhancement in the brainstem and cerebellum on magnetic resonance imaging, and perivascular lymphocytes and macrophages infiltrates on brain biopsies. Despite an initially good response to corticosteroids, all patients eventually became steroid‐dependent or ‐resistant, with frequent relapses on maintenance immunosuppressive therapy. Natalizumab and intravenous immunoglobulin stopped neurological disease progression in Patient 1 but he died at 17 years from respiratory complications. Patient 2 went into remission on infliximab and intravenous methylprednisolone for several months but was then diagnosed with Epstein–Barr virus driven B‐cell lymphoma 3 years after symptom onset. Patient 3 failed to respond to treatment and died 4 years after diagnosis. CLIPPERS disease in children is aggressive, with poor response to immunotherapy. Earlier use of newer immunotherapeutic agents such as natalizumab may be beneficial. Potential side effects need to be considered carefully. What this paper adds: Paediatric chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) appears a more severe condition than previously reported in adults. Aggressive treatment before neuroaxonal loss may be required for a better outcome. What this paper adds: Paediatric chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) appears a more severe condition than previously reported in adults. Aggressive treatment before neuroaxonal loss may be required for a better outcome. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Tobin on pages 391–392 of this issue. Resumen: ¿Es la inflamación linfocítica crónica con realce perivascular pontino sensible a los esteroides (CLIPPERS) en los niños con la misma condición que en los adultos?: Esta serie de casos describe a tres niños con inflamación linfocítica crónica con realce pontinal perivascular sensible a esteroides (CLIPPERS), una enfermedad inflamatoria caracterizada por un curso de enfermedad recurrente‐remitente sensible a los esteroides. Los pacientes (dos varones, edad 3 y 13 años, una mujer, edad 14 años) presentaron ataxia, disartria y neuropatías craneales múltiples. Todos los pacientes demostraron lesiones nodulares bilaterales con realce de contraste en el tallo cerebral y el cerebelo en imágenes de resonancia magnética y linfocitos perivasculares y infiltrados de macrófagos en biopsias cerebrales. A pesar de una respuesta inicialmente buena a los corticosteroides, todos los pacientes finalmente se volvieron dependientes de esteroides o resistentes, con recaídas frecuentes en la terapia inmunosupresora de mantenimiento. El natalizumab y la inmunoglobulina intravenosa suspendieron la progresión de la enfermedad neurológica en el paciente 1, pero falleció a los 17 años por complicaciones respiratorias. El paciente 2 entró en remisión con infliximab y metilprednisolona por vía intravenosa durante varios meses, pero luego se le diagnosticó linfoma de células B dirigido por el virus de Epstein‐Barr, 3 años después del inicio de los síntomas. El paciente 3 no respondió al tratamiento y murió 4 años después del diagnóstico. La enfermedad de CLIPPERS en los niños es agresiva, con una respuesta deficiente a la inmunoterapia. El uso previo de agentes inmunoterápicos más nuevos como natalizumab puede ser beneficioso. Los posibles efectos secundarios deben considerarse cuidadosamente. Resumo: A inflamação linfocítica crônica com realce perivascular pontino responsiva a esteróides (CLIPPERS) é a mesma condição em crianças e adultos?: Esta série de casos descreve três crianças com inflamação linfocítica crônica com realce perivascular pontino responsiva a esteróides (CLIPPERS), uma condição inflamatória caracterizada por uma doença com curso remissivo‐recidivante responsive a esteróides. Os pacientes (dois meninos, idades 3 e 13 anos; uma menina, idade 14 anos) apresentaram ataxia, disartria, e múltiplas neuropatias craniais. Todos os pacientes demonstraram lesões nodulares bilaterais com realce no tronco cerebral e cerebelo ao exame ne ressonância magnética, e infiltrados perivasculares de linfócitos e macrófagos nas biópsias cerebrais. Apesar de uma resposta inicialmente boa aos corticoesteróides, todos os pacientes eventualmente se tornaram esteróide‐dependentes ou resistentes, com frequentes recidivas com manutenção de imunoterapia supressora. Natalizumab e imunoglobulina intravenosa interromperam a progressão neurológica da doença no Paciente 1, mas ele veio a óbito na idade de 17 anos devido a complicações respiratórias. O Paciente 2 entrou em remissão com infliximab e metilprednosolona intravenosa por vários meses, mas foi então diagnosticado com linfoma de células B causado por virus Epstein‐Barr 3 anos após o início dos sintomas. O Paciente 3 não respondeu ao tratamento e veio a óbito 4 anos após o diagnóstico. Patient 2 went into remission on infliximab and intravenous methylprednisolone for several months but was then diagnosed with Epstein–Barr virus driven B‐cell lymphoma 3 years after symptom onset. Patient 3 failed to respond to treatment and died 4 years after diagnosis. Interpretação: A doença CLIPPERS em crianças é agressiva, com pouca resposta à imunoterapia. O uso precoce de agentes imunoterapêuticos mais novos como natalizumab pode ser benéfico. Potenciais efeitos colaterais devem ser considerados com cautela.